Peran Dinas Koperasi dan UMKM Kota Medan terhadap Pelaku UMKM Dalam Upaya Memperluas Pasar Produk UMKM - Annisa Karimah; Zuhrinal M. Nawawi (IAI Nasional Laa Roiba Bogor, 2022)
The purpose of this study was to determine the role of the Department of Cooperatives towards MSME actors in an effort to expand the MSME product market in Medan City. The type of research used is descriptive qualitative. The data sources used are primary and secondary data sources related to the observations that have been made. Data collection techniques used three ways, namely observation, interviews and documentation. The data analyst used is an interactive model. The results of the study indicate that the Mayor of Medan wants the Medan City MSMEs to advance to class by expanding the MSME product market. The Cooperative Service arranges steps in the context of fostering and developing MSMEs in the city of Medan. Innovations carried out digitally are in collecting MSME data, educating and fostering MSME actors related to the digital economy as well as expanding the market for products through E-catalogs and also using the marketplace as a means of digital marketing. Keywords: Role, Cooperatives & SMEs, Product Market Expansion Efforts.